Penerapan Keselamatan Dan Kesehatan Kerja Menggunakan Metode HIRADC Pada Struktur Bawah Gedung DPRD Manokwari Selatan: Application of Occupational Safety and Health Using the HIRADC Method on the Lower Structure of the South Manokwari DPRD Building - Aprisillia K. Susilo; Mayang K. F. Puteri; Lion F. Marini (JISTECH: Journal of Information Science and Technology, 2023)
The number of work accidents in the construction sector in the world is generally higher than the number of accidents in other sectors such as the manufacturing and industrial sectors due to the lack of K3 construction experts as well as the low awareness of workers in the field. Therefore, the K3 program is implemented to prevent work accidents. The purpose of this research is to be able to identify a hazard, analyze work risks, and determine controls using the HIRADC method on the lower structure of the South Manokwari Regional House of Representatives building. This study used a qualitative analysis method by carrying out and making observations in the field, distributing questionnaires to 8 informants, and interviewing the main informants, namely K3 experts. Based on the results of an analysis of the lower structure of the South Manokwari Regency Regional House of Representatives building, 141 accident risks were identified for each job with a percentage of the risk level before control was carried out, namely extreme risk (E) of 16,31%, high risk (H) of 35,46%, moderate risk (M) of 45,39%, and Low risk (L) of 2,84%. These results are still very high, so it is necessary to carry out a control. After controlling, the risk level decreased drastically, and at safe limits, the results were: extreme risk (E) of 0,00%, high risk (H) of 0,00%, moderate risk (M) of 19,15%, and Low risk (L) of 80,85%.